2021
DOI: 10.3390/app11135916
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Extraction Process in Non-Compliant ‘Bravo de Esmolfe’ Apples towards the Development of Natural Antioxidant Extracts

Abstract: The ‘Bravo de Esmolfe’ apple (BE) is rich in antioxidants and represents one of the most important traditional cultivars in Portugal. A large amount of non-compliant BE, with no market value, it is generated every year. Thus, an effort to find value-added solutions is of utmost importance. For the first time, green extraction (microwave-assisted-extraction (MAE) and ultrasound-assisted-extraction (UAE)) were compared against conventional extraction (with (CET) and without temperature (CE)) to select the most e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Apples are associated with the reduction in various diseases such as certain cancers In the 'Bravo de Esmolfe' apple, an autochthonous variety from Portugal, fifteen different phenolic compounds were identified, including three epicatechins, two caffeoylquinic acids, two procyanidins, two coumaroylquinic acids, (−)-epicatechin, phloretin-2-O-xyloglucoside, and phlorizin [4]. According to Vilas-Boas et al [28], 'Bravo de Esmolfe' is rich in antioxidants and represents one of the most important traditional varieties in Portugal. This study demonstrated that by applying a sustainable extraction technique, it was possible to obtain an antioxidant extract with higher antioxidant activity and polyphenols, including hydroxycinnamic acids (4-caffeoylquinic acid and 5-caffeoylquinic), flavanols (−)-epicatechin, (+)-catechin, and procyanidins), and chalcone (phoretin and phloridzin) [28].…”
Section: Applesmentioning
confidence: 99%
See 1 more Smart Citation
“…Apples are associated with the reduction in various diseases such as certain cancers In the 'Bravo de Esmolfe' apple, an autochthonous variety from Portugal, fifteen different phenolic compounds were identified, including three epicatechins, two caffeoylquinic acids, two procyanidins, two coumaroylquinic acids, (−)-epicatechin, phloretin-2-O-xyloglucoside, and phlorizin [4]. According to Vilas-Boas et al [28], 'Bravo de Esmolfe' is rich in antioxidants and represents one of the most important traditional varieties in Portugal. This study demonstrated that by applying a sustainable extraction technique, it was possible to obtain an antioxidant extract with higher antioxidant activity and polyphenols, including hydroxycinnamic acids (4-caffeoylquinic acid and 5-caffeoylquinic), flavanols (−)-epicatechin, (+)-catechin, and procyanidins), and chalcone (phoretin and phloridzin) [28].…”
Section: Applesmentioning
confidence: 99%
“…According to Vilas-Boas et al [ 28 ], ‘Bravo de Esmolfe’ is rich in antioxidants and represents one of the most important traditional varieties in Portugal. This study demonstrated that by applying a sustainable extraction technique, it was possible to obtain an antioxidant extract with higher antioxidant activity and polyphenols, including hydroxycinnamic acids (4-caffeoylquinic acid and 5-caffeoylquinic), flavanols (−)-epicatechin, (+)-catechin, and procyanidins), and chalcone (phoretin and phloridzin) [ 28 ].…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…As previously mentioned, the temperature seems to have an important impact on the extraction of phenolic compounds. The warmth may cause the plant tissues to soften and the bindings between polysaccharides and/or proteins and phenolic compounds to weaken, which could cause disruption and migration to the solvent [32]. However, because homogenous heating might be achieved more quickly and with less energy usage thanks to the energy transmission mechanism, MAE heating has been found to offer greater benefits than convection.…”
Section: Total Phenolic Contentmentioning
confidence: 99%
“…However, the process parameters (power, temperature, and time) play an important role in the impact of the final beverage quality, although the effects and energy balance as well established, the industrial application of MW is still limited by the lack of know-how concerning the chemical and biochemical impact on the food matrix. Furthermore, the use of microwave energy in combination with controlled temperature and pressure allows for the high diffusion of fluids and may be applied to different matrices to extract BCs or to increase the bio-accessibility of BCs in the food matrix; thus, it could produce functional beverages [ 74 , 75 ].…”
Section: Beverage Processing Technologiesmentioning
confidence: 99%